The National SOM Survey 2006 - SOM Institute, University of Gothenburg (University of Gothenburg, 2008)
Since 1986 the SOM-institute has been carrying out an annual nation-wide survey of Swedish opinions. This is accordingly the twentyfirst survey in this series. The SOM-institute is a collaboration between three departments at Göteborg University: the Institute for Journalism and Mass Communication, the Department of Political Science, and the School of Public Administration. Since 1998 the survey includes two nation representative samples and uses two different mail questionnaires. One of the questionnaires mainly deals with questions on politics, economy and working life, while the other mainly deals with media, culture and health.

In 2006 approximately one fourth of the questions asked in the two questionnaires are common for both samples, for example questions about media habits, political attitudes, leisure activities, and social background. The questionnaire on politics include ten different subject fields: news and media; politics, society and democracy; Sweden's relations to the surrounding world; possession of technical equipment and internet; society and public service; environment and energy; knowledge and society; activities, interests, and values; work life; and background questions. The media questionnaire is divided into eleven subject fields: news and papers; politics, society and democracy; television and radio; possession of technical equipment, internet and mobile telephony; periodicals, books and libraries; movies and theatre; media and society; the dog in society; activities, interests, and values; work life and background questions.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den tjugoförsta undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

Riks-SOM 2006 genomfördes som två undersökningar med två representativa urval och två olika formulär, där datainsamlingarna genomfördes parallellt och under identiska förhållanden. Frågeformulären skiljer sig något åt i det att tyngdpunkten i det ena formuläret ligger på politik och samhälle, medan det andra har en tonvikt på frågor om medier, kultur och livsstil. Ungefär en fjärdedel av frågorna är gemensamma för de båda frågeformulären och kan därmed analyseras med dubbla urvalsstorleken som grund.

Politikformuläret (Riks-1) innehåller tio olika frågeområden: nyheter och medier; politik, samhälle och demokrati; Sveriges förhållande till omvärlden; teknikinnehav och internet; samhälle och service; miljö och energi; kunskap och samhälle; aktiviteter, intressen och värderingar; arbetsliv; samt bakgrundsfrågor. Medieformuläret (Riks-2) tar upp elva frågeområden: nyheter och tidningar; politik, samhälle och demokrati; TV och radio; teknikinnehav, internet och mobiltelefoni; tidskrifter, böcker och bibliotek; film och teater; medier och samhälle; hunden i samhället; aktiviteter, intressen och värderingar; arbetsliv; samt bakgrundsfrågor.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 2006
Riks-SOM 2006
Keywords: mass media; massmedia; population migration; migration; energy; energi; environment; miljö; health; hälsa; leisure time; fritid; trust; förtroende; environmental conservation; miljöbevarande; voting; röstning; european union; europeiska unionen; political interest; politiskt intresse; local government services; kommunal service; nuclear energy; kärnkraft; newspaper readership; tidnings läsekrets; periodicals readership; tidskrifts läsekrets; membership; medlemskap; drinking behaviour; alkoholvanor; cinema attendance; biobesök; party identification; partiidentifikation; information sources; informationskällor; book use; bokanvändning; television channels; tv-kanaler; television advertising; tv-reklam; news; nyheter; television programmes; tv-program; theatre attendance; teaterbesök; energy policy; energipolitik; radioactive wastes; radioaktivt avfall; professional ethics; yrkesetik; privatization; privatisering; journalism; journalistik; taxation; beskattning; television viewing; tv-tittande; research; forskning; religious affiliation; religiös tillhörighet; language skills; språkfärdigheter; internet; internet; internet access; internetåtkomst; audio and video equipment; ljud- och videoutrustning; mobile communication; mobilkommunikation; referendums; folkomröstningar; democracy; demokrati; internal politics; inrikespolitik; political parties; politiska partier; political leaders; politiska ledare; clubs; föreningar; leisure time activities; fritidsaktiviteter; radio listening; radiolyssnande; CORS; CORS; Media; Media